Effect of Mamao Pomace Extract on Insulin Resistance in Type 2 Diabetic Rats. - Mungkhunthod, Sootthikarn; Tangsucharit, Panot; Senggunprai, Laddawan; Sripui, Jintana; Kukongviriyapan, Upa; Pannangpetch, Patchareewan (Srinagarind Medical Journal, 2015)
Background and Objective: High fat diet (HFD) can cause insulin resistance which plays a major pathogenic role in the development of type 2 diabetes mellitus. Interestingly, an in vitro antihyperglycemic activity of Mamao (Antidesma thwaitesianum Müll. Arg) has been reported including anti-alpha-amylase and anti-alpha-glucosidase. Thus, this study aimed to investigate the effect of Mamao pomace ethanolic extract (MPE) on insulin resistance, blood glucose, lipid profiles and serum adipokines in HFD/Streptozotocin (STZ)-induced type 2 diabetic rats. Methods: Male Sprague-Dawley rats were fed HFD (60% lard oil) throughout the experiment. Normal control rats were fed normal chow. At week 4 of HFD feeding, STZ 30 mg/kg was injected intraperitoneally. Two weeks after STZ injection, treatments were applied for further six weeks as followed: Group I: distilled water (diabetic control); Group II-IV: MPE 250, 500 and 1000 mg/kg respectively; Group V: pioglitazone 10 mg/kg. Then, fasting blood glucose (FBG), oral glucose tolerance test (OGTT), serum insulin, serum adiponectin and lipid profiles were examined. Homeostasis Model Assessment-Insulin Resistance (HOMA-IR), an indicator of insulin resistance was calculated. Results: MPE (500 and 1000 mg/kg) significantly decreased the FBG and improved OGTT as compared to DM-control group (p<0.05). HOMA-IR score of DM rats receiving MPE was significantly decreased whereas serum adiponectin was significantly increased as compared to DM control. Moreover, MPE significantly lowered serum total cholesterol, triglyceride<a href="https://www.google.co.th/url?sa=t&rct=j&q=&esrc=s&source=web&cd=1&sqi=2&ved=0CBwQFjAAahUKEwipj6jf36jHAhXNVY4KHdfpAMI&url=http%3A%2F%2Fwww.siamhealth.net%2Fpublic_html%2FHealth%2FLab_interprete%2Fldl.html&ei=U_bNVemZOM2ruQTX04OQDA&usg=AFQjCNFXFEbyS9IWhVJ-xPCLbIvkPIPh4A&sig2=YBH0RmedLezBMr-yK5mjwQ&bvm=bv.99804247,d.c2E&cad=rja">, and raised high-density lipoprotein cholesterol (HDL). Conclusion: The results indicate that MPE improves insulin resistance, hyperglycemia and lipid profiles in type 2 diabetic rats, possibly via its adiponectin secretion-enhancing effect.